Research Status of Silver Nanoparticles for Dental Applications - Yanyan Guo; Xiaomei Hou; Sanjun Fan; Chanyuan Jin (Inorganics)
Silver nanoparticles (AgNPs) have emerged as a promising antimicrobial agent in dentistry due to their distinctive physicochemical characteristics and broad-spectrum biocidal activity. For example, silver nanoparticles can be incorporated into oral hygiene products in preventive dentistry, composite resins in restorative treatment, irrigation solutions in endodontic treatment, membranes for guided tissue regeneration in periodontal treatment, acrylic resins and porcelains in prosthodontic treatment, coatings in dental implant treatment, and brackets and wires in orthodontic treatment. This paper focuses on summarizing the current knowledge on the antimicrobial use of silver nanoparticles in dentistry, highlighting their antimicrobial mechanism and potential applications in clinical treatment. The literature indicates that silver nanoparticles are a promising antimicrobial agent in dentistry. However, there are still many issues including fundamental antibacterial mechanisms that need to be completely elucidated before clinical applications.